KARAKTERISASI DAN APLIKASI ANTIBODI MONOKLONAL WDSSB5 UNTUK DETEKSI VIRUS DENGUE PADA SEL C6/36 DENGAN METODE IMUNOSITOKIMIA - Kiki Deniati; Ria Anugrahwati; Tini Suminarti (Holistik Jurnal Kesehatan, 2019)
THE INFLUENCES OF CRITICALLY THINKING TO THE SKILL OF NURSE ASSOCIATE IN CONDUCTING THE NURSING CARE AT HERMINA HOSPITAL IN BEKASI 2016This study proposed to figure out the influences of crirically thinking to the skill of nurse assosiate in conduction the nursing care at Hermina Hospital in Bekasi. The type of this study is quantitative method with the cross sectional approach. The samples of the study were 104 nurse assosiate with the total sampling technique. The statistical analysis used the chi square. The influences of critically thinking to the skill of nursing assosiet in conducting the nursing care (p= 0,026). was the result of the study the nursing that thought critically got the chances of 2,403 times more than less crirically thinking nurses. To the future the hopitacal can developing journal reading programme and to make it of reading habbit national and international research to be improvement knowledge and need for nurses associate that it can inereating skill crtical throw nursing round.